Professional knowledge and the epistemology of reflective practice - Kinsella, Elizabeth Anne (Nursing philosophy, 2010)
Reflective practice is one of the most popular theories of professional knowledge in the last 20 years and has been widely adopted by nursing, health, and social care professions. The term was coined by Donald Schön in his influential books The Reflective Practitioner, and Educating the Reflective Practitioner, and has garnered the unprecedented attention of theorists and practitioners of professional education and practice. Reflective practice has been integrated into professional preparatory programmes, continuing education programmes, and by the regulatory bodies of a wide range of health and social care professions. Yet, despite its popularity and widespread adoption, a problem frequently raised in the literature concerns the lack of conceptual clarity surrounding the term reflective practice. This paper seeks to respond to this problem by offering an analysis of the epistemology of reflective practice as revealed through a critical examination of philosophical influences within the theory. The aim is to discern philosophical underpinnings of reflective practice in order to advance increasingly coherent interpretations, and to consider the implications for conceptions of professional knowledge in professional life. The paper briefly examines major philosophical underpinnings in reflective practice to explicate central themes that inform the epistemological assumptions of the theory. The study draws on the work of Donald Schön, and on texts from four philosophers: John Dewey, Nelson Goodman, Michael Polanyi, and Gilbert Ryle. Five central epistemological themes in reflective practice are illuminated: (1) a broad critique of technical rationality; (2) professional practice knowledge as artistry; (3) constructivist assumptions in the theory; (4) the significance of tacit knowledge for professional practice knowledge; and (5) overcoming mind body dualism to recognize the knowledge revealed in intelligent action. The paper reveals that the theory of reflective practice is concerned with deep epistemological questions of significance to conceptions of knowledge in health and social care professions.